PENDAPATAN USAHATANI TEBU RAKYAT DAN POLA KEMITRAAN PADA PETANI MITRA PT BUMA CIMA NUSANTARA, KABUPATEN LAMPUNG UTARA - Safira Puspa Nusa; Dwi Haryono; Yuliana Saleh (Lampung University, 2021)
The objectives of this research were to find out the income of sugar cane farming and the implement of partnership pattern between PT Buma Cima Nusantara and partner farmers in Bunga Mayang Sub-District, North Lampung Regency. The location was determined purposively, considering that Bunga Mayang Sub-District has been the center of sugar cane production in North Lampung Regency. The number of respondents in this research were 66 respondents and taken randomly. Data were collected from January to February 2020. The analytical methods that used were farm income analysis and descriptive qualitative analysis. The study shows that the average income for total cost of sugar cane farming is Rp12,056,030.40/hectare and the R/C ratio is 1.49. The partnership pattern that PT Buma Cima Nusantara and partner farmers implemented is a agribusiness operational cooperation partnership pattern, where the sugar cane farmers act as a group of partners that provide land, facilities, and labors and PT Buma Cima Nusantara acts as a partner company that provides costs, capital, management, procurement of production facilities, and the guarantor of the product market.Key words: income, partnership, sugar cane farming